Molecular Epidemic Characteristics and Genetic Evolution of Porcine Circovirus Type 2 (PCV2) in Swine Herds of Shanghai, China - Le Kang; Abdul Wahaab; Kun Shi; Bahar E Mustafa; Yan Zhang; Junjie Zhang; Zongjie Li; Yafeng Qiu; Beibei Li; Ke Liu; Donghua Shao; Zhiyong Ma; et al. (Viruses, 2022)
Porcine Circovirus 2 (PCV2) is a crucial swine pathogen and considered a primary causative agent of porcine circovirus-associated diseases (PCVADs), posing a serious economic threat to the swine industry across globe. The world’s biggest agricultural conglomerates have teamed up to create giant commercial pig farms across Shanghai due to the proximity of this region to more affluent lean-pork markets. Since its discovery, PCV2 has displayed extraordinary genetic diversity, and its genome is swiftly evolving through a series of mutations and recombinations. However, limited information on epidemiology, molecular characteristics, vaccine cross-protection, and the co-infection rate of PCV2 with other lethal swine diseases can adversely impact the pig production in the region. To investigate the molecular epidemic characteristics and genetic evolution of PCV2, pigs with doubtful symptoms of PCVADs were sampled from various commercial pig farms with a history of PWMS and/or PDNS across Shanghai from 2014 to 2018. Our results revealed the coexistence of multiple PCV2 genotypes (PCV2b, PCV2e, and PCV2d) among Shanghai pig herds and dominance of PCV2d among them. We also found critical amino acid substitutions in epitope regions of important capsid proteins in PCV2 isolates involved in viral replication and host immune escape. Spotted mutations may favor the prevalence and survival of various PCV2 genotypes despite availability of commercial vaccines. This study also provides insight into the co-infection status of PCV2 with major lethal swine viral diseases such as PPV and PPRSV. Collectively, these investigations will contribute to understanding the molecular epidemiology and evolution of PCV2 across the region.